Mutants in a yeast Ran binding protein are defective in nuclear transport. - Schlenstedt, G (1995)
Ran, a Ras-like GTPase, has been implicated in controlling the movement of proteins and RNAs in and out of the nucleus. We have constructed strains of Saccharomyces cerevisiae which produce fusion proteins containing glutathione-S-transferase (GST) fused to Gsp1p, which encodes the essential yeast Ran homolog, and a mutant form of Gsp1p that mimics the GTP-bound state. A major protein with the apparent size of 34 kDa co-purifies with the GTP-bound form of Gsp1p. This protein was identified as Yrb1p (Yeast Ran Binding Protein) and stimulates GTP hydrolysis by Gsp1p in the presence of Rna1p, the Gsp1 GTPase activating protein. Yrb1p is located in the cytoplasm with some concentration at the nuclear periphery. Temperature-sensitive yrb1 mutants are defective in nuclear protein import and RNA export. A mutation in the highly conserved Ran binding region of Yrb1p reduces its ability to interact with Gsp1p. These data indicate that Yrb1p functions with Gsp1p and suggest that together they can control transport of macromolecules across the nuclear envelope.